2023
DOI: 10.1039/d2ob01875f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the application of Langlois’ reagent in olefin difunctionalization

Abstract: In this review, we summarise the recent applications of Langlois’ Reagent in the radical-mediated difunctionalization of alkenes. Among the various trifluoromethylation reagents, Langlois’ Reagent is an exceptional compound, and many...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…Radical addition, coupling, rearrangement, and cleavage reactions are powerful in the synthesis of diverse molecular structures [ 1 , 2 ]. Difunctionalization reactions initiated with radical addition are attractive for both synthetic efficiency and product diversity considerations [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. We have recently reported radical 1,2-difunctionalization ( Scheme 1 I) [ 13 ] and addition-/cyclization-based difunctionalization reactions ( Scheme 1 II) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radical addition, coupling, rearrangement, and cleavage reactions are powerful in the synthesis of diverse molecular structures [ 1 , 2 ]. Difunctionalization reactions initiated with radical addition are attractive for both synthetic efficiency and product diversity considerations [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. We have recently reported radical 1,2-difunctionalization ( Scheme 1 I) [ 13 ] and addition-/cyclization-based difunctionalization reactions ( Scheme 1 II) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trifluoromethylation, especially, is an attractive and powerful method of introducing fluorine into organic motifs, due to the vast number of trifluoromethyl (CF 3 ) reagents that have emerged over the past few decades (Figure a). , However, despite the variety, a majority of CF 3 reagents are very expensive, causing them to be limited in commercial accessibility . Trifluoromethyltrimethylsilane (TMSCF 3 , also known as Ruppert–Prakash reagent) has been an effective solution to this end, serving as an inexpensive nucleophilic CF 3 source when paired with an anionic initiator such as a fluoride source or a strong base (Figure b). , Another attractive solution to this problem is sodium triflinate (CF 3 SO 2 Na, also known as Langlois reagent), which is an inexpensive, bench-stable, white solid which allows convenient handling and easy storage . Sodium triflinate can serve as a radical CF 3 source via desulfonylation upon a single-electron oxidation, typically achieved in thermal processes through (super)stoichiometric amounts of peroxides. Additionally, it was revealed that sodium triflinate could also be activated via photocatalysis in oxidant-free conditions, demonstrated by a radical trifluoromethylation of styrenes. On the other hand, independent works from Li and MacMillan demonstrated the use of aliphatic carboxylic acids as alkyl precursors in decarboxylative trifluoromethylation (Figure c). , While organosulfinates have been paired with carboxylic acid derivatives to photocatalytically generate sulfones, the use of sodium triflinates in decarboxylative C(sp 3 ) trifluoromethylation has not been studied before .…”
Section: Introductionmentioning
confidence: 99%
“…10,12−14 Another attractive solution to this problem is sodium triflinate (CF 3 SO 2 Na, also known as Langlois reagent), which is an inexpensive, bench-stable, white solid which allows convenient handling and easy storage. 15 Sodium triflinate can serve as a radical CF 3 source via desulfonylation upon a single-electron oxidation, typically achieved in thermal processes through (super)stoichiometric amounts of peroxides. 16−20 Additionally, it was revealed that sodium triflinate could also be activated via photocatalysis in oxidant-free conditions, demonstrated by a radical trifluoromethylation of styrenes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the contrary, Langlois reagent is a self-stable, easily available, relatively cheaper CF 3 -source for oxidative trifluoromethylation reactions. 13 As part of our ongoing research in electrochemistry, 14 herein, we report a mediator-free electro-oxidative trifluoromethylation of β,γ-unsaturated oximes followed by tandem cyclization constructing trifluoro-methylated isoxazolines using Langlois reagent (Scheme 1c).…”
mentioning
confidence: 99%